Pengaruh Model PBL dengan Pendekatan Pembelajaran Diferensiasi Materi Gotong Royong Siswa Kelas IV SD Swasta YP HKBP 1 Pematangsiantar - Yosua Marasi Parningotan Siagian; Cholifah Tur Rosidah; Rosmiati Rosmiati (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study is motivated by the low academic performance of fourth-grade students in Pancasila Education, specifically in the topic of mutual cooperation. The aim of this research is to assess the improvement in learning outcomes for fourth-grade students in Pancasila Education through the implementation of the Problem Based Learning (PBL) model with a Differentiation approach. This research falls under the category of classroom action research and was conducted in two cycles. The subjects of the study were 28 fourth-grade students from SD YP HKBP 1 Pematangsiantar. Data were collected through observations and tests, and then analyzed using descriptive quantitative methods. The results indicate that the implementation of the PBL model with a Differentiation approach successfully improved student learning outcomes in the topic of mutual cooperation. The average student performance was 57.14 during the pre-cycle. After implementing the PBL model in cycle I, the average score increased to 71.42, and in cycle II, it rose further to 84.72. Based on these results, it can be concluded that the PBL model with a Differentiation approach is effective in enhancing the learning outcomes of fourth-grade students on the topic of mutual cooperation at SD YP HKBP 1 Pematangsiantar.